MAXILLARY SINUSITIS OF ODONTOGENIC ORIGIN - Dumitru Hîțu; Nicolae Chele; Dumitru Șcerbatiuc; Vasile Cabac; Alexandru Mighic; Bădărău Lilia (Romanian Society of Oral Rehabilitation, 2020)
We present a retrospective study, which was performed on a batch of 177 patients diagnosed with maxillary sinusitis, selected from the total number of patients with OMF disorders during 2017-2018. The patients were examined and treated at the Department of Emergency Medicine of the Institute of Emergency Medicine, Chisinau. The article contains statistical data on odontogenic maxillary sinusitis and the breakdown by age, sex, profession, etiology, addressability, place of life, hospitalization, causal tooth and treatment methods. Results: Out of the total number of 3227 patients with OMF, maxillary sinusitis (5.48%) was established for 177 patients. The majority of the patients 52.54% are from Chisinau. The most affected are the patients aged 31-40 years, constituting 26.56%, the majority being male persons 63.27%. Admission to the medical institution prevailed for 74.01% of the cases by itself, and the medical insurance was presented for 77.97%. Hospitalization of patients ranged from 1-5 days to 55.35%. The frequency of teeth involved in the inflammatory processes of the sinus was 41.78% cases, of which 1st molar prevails with 23.16%, thus being an etiological factor. As a surgical treatment of maxillary sinusitis in the section of oro-maxillofacial surgery, radical cure is used for 58.75% cases.